The implementation of social policies in a pandemic context: an analysis of anger - Andrea Dettano; Rebeca Cena (Social Work and Society)
The pandemic context put into operation social policies that sought to accompany the difficulties in earning an income. Against this background, social policies acquired a visible centrality in state agendas, dedicated to dealing with the health emergency caused by COVID-19. In the Argentine case, a policy called Emergency Family Income (EFI) was implemented, consisting of a cash transfer intended to mitigate the loss of income generated by Social, Preventive, and Compulsory Isolation (SPCI). The EFI’s management, implementation, access, and collection method underwent a digitalisation process, enabling access through official and nonofficial channels. Among nonofficial channels there are Facebook Groups, where the beneficiaries of social policies exchange information, doubts, and advice. Its application and actual access encountered several obstacles and engendered different emotions. As part of a virtual ethnography in a Facebook group, this paper develops -from the social studies of emotions-, how anger unfolds in the collection of a social policy. The analysis of emotions in state interventions allows us to reformulate the study of the implementation processes. The main findings are 1) anger appears as a product of the mismatch between expectation and experience in the face of irregular operations in its implementation; 2) anger presents a binding and supportive character that is shared in the search for empathy and is reinforced by sharing it; 3) it is driven by the evaluations of deserving/not deserving subsidies 4) politicians and different leaders are regarded as legitimate recipients. The conclusions highlight the central place that anger holds in the implementation of social policies. Studying anger allows us to shed light on the obstacles and the practices involved in state interventions and thus improve the implementation processes of social policies based on the experiences of the recipient population. It also makes it possible to identify some guidelines for improving government interventions, such as help with digitalisation processes; provide clear and uniform information; comply with regular payments; assist recipients; and promote government transparency.